Adherence to dietary approaches to stop hypertension (DASH) and Mediterranean dietary patterns in relation to cardiovascular risk factors in older adults. (October 2020) - Jalilpiran, Yahya; Darooghegi Mofrad, Manije; Mozaffari, Hadis; Bellissimo, Nick; Azadbakht, Leila
Summary: Objective: The aging process is associated with several chronic diet-related complications, including cardiovascular diseases. Therefore, the objective was to examine the association between DASH and Mediterranean dietary pattern (MDP) on cardiovascular risk factors and inflammatory markers in older adult men. Methods: A cross-sectional study was performed on 357 older adult men who were randomly selected from health centers across Tehran, Iran. Dietary intakes, anthropometric measures, biochemical markers, and general characteristics were also collected. Multivariate logistic regression was used to estimate odds ratios of outcomes across medians of dietary patterns, respectively. Results: After adjusting for possible confounders, greater adherence to the MDP was associated with lower waist circumference, triacylglycerol, high-sensitivity c-reactive protein, fibrinogen, and higher HDL-C (p < 0.05). Greater adherence to the DASH diet was associated with lower fibrinogen (p < 0.05). Adherence to the MDP was inversely associated with diastolic blood pressure (OR, 0.35; 95% CI, 0.14–0.79; P = 0.01) and fibrinogen levels (OR, 0.33; 95% CI, 0.20–0.52; P < 0.001). Moreover, greater adherence to the DASH diet (second vs first category) was associated with reduced risk of high diastolic blood pressure (OR, 0.11; 95% CI, 0.04–0.34; P < 0.001), insulin levels (OR, 0.44; 95% CI, 0.28–0.72; P < 0.001), hs-CRP (OR, 0.53; 95% CI, 0.33–0.85; P = 0.009), and fibrinogen (OR, 0.37; 95% CI, 0.21–0.64; P < 0.001). Conclusion: There was an inverse association between the DASH and MDP with several cardiovascular risk factors. Future, longitudinal study designs are needed to confirm these results.